Fabio Parasecoli & Peter Scholliers, general editors: A Cultural History of Food - Thick, Malcolm (Petits Propos Culinaires, 2015)
Fabio Parasecoli & Peter Scholliers, general editors: A Cultural History of Food: Berg, 2012, 6 vols., hardback, £350.